Differentiating criminal networks in the illegal wildlife trade: organized, corporate and disorganized crime - Wyatt, Tanya (Trends in organized crime, 2020)
Historically, the poaching of wildlife was portrayed as a small-scale local activity in which only small numbers of wildlife would be smuggled illegally by collectors or opportunists. Nowadays, this image has changed: criminal networks are believed to be highly involved in wildlife trafficking, which has become a significant area of illicit activity. Even though wildlife trafficking has become accepted as a major area of crime and an important topic and criminologists have examined a variety of illegal wildlife markets, research that specifically focusses on the involvement of different criminal networks and their specific nature is lacking. The concept of a ‘criminal network’ or ‘serious organized crime’ is amorphous – getting used interchangeably and describes all crime that is structured rather than solely reflecting crime that fits within normative definitions of ‘organized’ crime. In reality, criminal networks are diverse. As such, we propose categories of criminal networks that are evidenced in the literature and within our own fieldwork: (1) organized crime groups (2) corporate crime groups and (3) disorganized criminal networks. Whereas there are instances when these groups act alone, this article will (also) discuss the overlap and interaction that occurs between our proposed categories and discuss the complicated nature of the involved criminal networks as well as predictions as to the future of these networks.